1996
DOI: 10.1038/bjc.1996.368
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in human cancer cell lines by the novel anthracenyl-amino acid topoisomerase I inhibitor NU/ICRF 505

Abstract: Summary Anthracenyl-amino acid conjugates represent a novel chemical class of topoisomerase (topo) inhibitor. NU/ICRF 505 is a lead compound that stabilises topo I cleavable complexes and is actively cytotoxic at low MM concentrations. In this study, endonucleolytic DNA cleavage was used as a marker of apoptosis to investigate mechanisms of cell death produced by this compound. NU/ICRF 505 (5 yM) induced a substantial increase in the level of DNA fragmentation in HL60 cells (up to 30% of total extracted DNA) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The DNA ladder assay conducted on Hep-2 cell lines showed that two active compounds viz., AMK OX-11 and AMK OX-12, produced fragmentation of DNA (apoptotic phenomenon) by ladder formation. Ladder formation is the marker of apoptotic phenomenon (Meikle et al 1996). The chemical nature of oxadiazoles would have to be suspected as causing DNA-damage leading to apoptosis induction in cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA ladder assay conducted on Hep-2 cell lines showed that two active compounds viz., AMK OX-11 and AMK OX-12, produced fragmentation of DNA (apoptotic phenomenon) by ladder formation. Ladder formation is the marker of apoptotic phenomenon (Meikle et al 1996). The chemical nature of oxadiazoles would have to be suspected as causing DNA-damage leading to apoptosis induction in cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…1] [4]. In continuation to our previous work, herein we report the detailed biological profiling of oxaspiro [4,5] trienones; II and azaspiro [4,5]trienones; III along with their structure activity relationship (SAR) studies. The literature survey shows that structurally related antitumor compounds bearing enone moiety may facilitate ROS production which in turn can induce apoptosis [ Fig.…”
Section: Introductionmentioning
confidence: 92%
“…A series of twenty seven oxa/azaspiro [4,5]trienone derivatives were synthesized and their anticancer properties have been explored. GI 50 values of all these compounds were evaluated against four types of human cancer cell lines, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] They were also shown to act by inhibiting topoisomerases I and II and appeared as promising new drugs. However, all of the previous compounds were lacking the hydroxyl groups in the aromatic planar system, characteristic of Mx and known to improve drug activity to a substantial extent.…”
Section: Introductionmentioning
confidence: 99%